Isolation, genomic characterization, and mushroom growth-promoting effect of the first fungus-derived Rhizobium - Hua, Zhongyi; Liu, Tianrui; Han, Pengjie; Zhou, Junhui; Zhao, Yuyang; Huang, Luqi; Yuan, Yuan (Frontiers in Microbiology, 2022)
Polyporus umbellatus is a well-known edible and medicinal mushroom, and some bacteria isolated from mushroom sclerotia may have beneficial effects on their host. These mushroom growth-promoting bacteria (MGPBs) are of great significance in the mushroom production. In this work, we aimed to isolate and identify MGPBs from P. umbellatus sclerotia. Using the agar plate dilution method, strain CACMS001 was isolated from P. umbellatus sclerotia. The genome of CACMS001 was sequenced using PacBio platform, and the phylogenomic analysis indicated that CACMS001 could not be assigned to known Rhizobium species. In co-culture experiments, CACMS001 increased the mycelial growth of P. umbellatus and Armillaria gallica and increased xylanase activity in A. gallica. Comparative genomic analysis showed that CACMS001 lost almost all nitrogen fixation genes but specially acquired one redox cofactor cluster with pqqE, pqqD, pqqC, and pqqB involved in the synthesis of pyrroloquinoline quinone, a peptide-derived redox participating in phosphate solubilization activity. Strain CACMS001 has the capacity to solubilize phosphate using Pikovskaya medium, and phnA and phoU involved in this process in CACMS001 were revealed by quantitative real-time PCR. CACMS001 is a new potential Rhizobium species and is the first identified MGPB belonging to Rhizobium. This novel bacterium would play a vital part in P. umbellatus, A. gallica, and other mushroom cultivation.